A psychometric analysis of the Approaches to Teaching Inventory (ATI) and a proposal for a Spanish version (S-ATI-20) - Monroy, Fuensanta; González-Geraldo, José L.; Hernández-Pina, Fuensanta (Anales de Psicología / Annals of Psychology, 2014)
Background: Recent educational research has explored how university teachers approach their teaching. One of the most widely used instruments is Trigwell and Prosser´s (2004) Approaches to Teaching Inventory (ATI). There is, however, scarce research on the Spanish version of this questionnaire. This paper aimed: 1) to analyse the reliability and structural validity of two existing versions of ATI in Spanish language, and 2) to present a proposal for a new Spanish version of ATI, and to measure its reliability and validity. Method: The samples comprised university and trainee teachers from two Spanish universities. Results: Reliability coefficients, factor structures, and item loadings of the two existing Spanish versions of ATI were evaluated. Some coincidental outcomes suggested that a revised ATI in Spanish was required, thus a new version (S-ATI-20) was presented and tested on a new sample. Conclusions: The results suggest questionnaires should be suitably translated and item wording carefully adapted. Factor analyses moderately support a two-scale model, but a lack of correlation between approaches suggests alternative approaches to teaching models might be worth considering. This paper presents preliminary results which should be taken with caution, but S-ATI-20 may serve as a tool for self-reflection in faculty development.